Preparation of Floating Gel Beads and Their Performance in Degrading Fluoroquinolone Antibiotics - Pendergast, Erik; Ladder, Suhas; Kotov, Anna (Journal of Functional Materials and Applied Engineering, 2024)
The abuse of Fluoroquinolone antibiotics (FQs) has led to their frequent detection in water environments, posing serious ecological risks and health hazards. Among various treatment technologies, photocatalytic technology is a green, efficient, and promising method for water pollution remediation. Efficient separation of photogenerated charge carriers is a key driving force for photocatalytic reactions, and the amount of reactive oxygen species (ROS) generated determines the catalytic performance of photocatalysts. However, traditional micro/nano powder photocatalysts face challenges such as slow O₂ transport at the solid-liquid interface, low light utilization, severe agglomeration, and difficulties in collection and recycling, which greatly limit their large-scale application in water pollution remediation. Therefore, this study constructed a heterojunction and established a floating catalytic system to prepare photocatalytic gel beads (CA/CNF@BiOBr/Ti₃C₂) with a hollow porous structure, which simultaneously possesses favorable mass transfer properties and effective catalytic active centers. These gel beads can mineralize various FQs, resist interference from complex water environments, and exhibit excellent stability. The specific research results are as follows:CA/CNF@BiOBr/Ti₃C₂ photocatalytic gel beads with a particle size of approximately 2.2 mm and a hollow porous structure were prepared using an ion-gelation dropwise injection method. Benefiting from the hydrogen bonding between the terminal groups on Ti₃C₂ and the abundant oxygen-containing groups (e.g., -COOH and -OH) on CA/CNF, BiOBr/Ti₃C₂ powder was successfully immobilized on the CA/CNF organic carrier. The photocatalytic removal rates of CA/CNF@BiOBr/Ti₃C₂ gel beads for several FQs—moxifloxacin (MOX), norfloxacin (NOR), enrofloxacin (ENR), lomefloxacin (LOM), levofloxacin (LEV), and ofloxacin (OFL)—reached 92.1%, 86.3%, 87.0%, 85.4%, 89.0%, and 90.1%, respectively. After 10 cycles of use, the gel beads maintained high degradation efficiency, resisted interference from various common ions and organic matter in water bodies, adapted to extreme pH environments, and effectively prevented Bi³⁺ leaching.